Pembelajaran Organisasi Industri Pada Struktur Perilaku Ekonomi Kota Cirebon - Muhammad Yasin; Erwin Putra R.D; Mahindah Mahindah; Melkior Keleka Hayon (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Industrial organization learning is an important concept in economics that understands how companies and markets interact in an industry. Since the implementation of AEC on January 1 2016, every country has tried to be able to compete and maintain the survival of business organizations in their respective countries. Each country is free to market its products to other countries so that each country competes to produce products that can be marketed in other countries. a relevant concept in the context of the structure of economic behavior, which includes how companies compete, collaborate, and respond to market dynamics.